2006
DOI: 10.1590/s0101-81752006000100024
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do mecanismo de transposição de peixes da Usina Hidrelétrica Santa Clara por camarões (Palaemonidae), bacia do rio Mucuri, Minas Gerais, Brasil

Abstract: Durante a operação do elevador para peixes da Usina Hidrelétrica Santa Clara, de novembro de 2003 a março de 2004, todos os crustáceos palaemonídeos adultos que utilizaram o mecanismo foram contados e o número de jovens estimado. Duas espécies foram registradas: Macrobrachium carcinus (Linnaeus, 1758) e Macrobrachium acanthurus (Wiegmann, 1836). A utilização do mecanismo por adultos foi bastante restrita, com apenas 185 exemplares registrados. Porém, o número de jovens de M. carcinus utilizando o elevador foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hamano & Honke (1997) showed how floodlight illumination of one bank can be used to direct migrating shrimps, which avoid such light, to the opposite bank below a dam equipped with a fishway. Pompeu et al (2006) reported that juvenile migraters enter and are transported to the upstream side of power plant dam with a fish lift (elevator). If dams or other obstacles are low enough, continual or periodic flow over the structure will stimulate juvenile movement over them.…”
Section: Occurrence and Reduction Of Human Impactsmentioning
confidence: 99%
“…Hamano & Honke (1997) showed how floodlight illumination of one bank can be used to direct migrating shrimps, which avoid such light, to the opposite bank below a dam equipped with a fishway. Pompeu et al (2006) reported that juvenile migraters enter and are transported to the upstream side of power plant dam with a fish lift (elevator). If dams or other obstacles are low enough, continual or periodic flow over the structure will stimulate juvenile movement over them.…”
Section: Occurrence and Reduction Of Human Impactsmentioning
confidence: 99%